Holistic Management of A 55-year-old Female Patient with Benign Paroxysmal Positional Vertigo through Family Medicine Approach - Avisa Jinan Azura; Diana Mayasari (Fakultas Kedokteran Universitas Lampung, 2025)
Vertigo is defined as a postural awareness disorder and can be a feeling of spinning in oneself or the surrounding environment. According to WHO, vertigo often occurs at the age of 18-79 years with a global prevalence of 7.4% and an annual incidence of 1.4%. This study employs a holistic and comprehensive family medicine approach to identify risk factors, clinical issues, and to guide patient management, grounded in evidence-based practices. The approach integrates a family-focused, patient-centered, and community-oriented perspective. The analysis is presented in the form of a case report. Primary data were collected through anamnesis and physical examination, while secondary data were sourced from the patient's medical records at the Health Center. The evaluation was conducted using a holistic diagnostic framework, encompassing the initial, processual, and concluding phases of the study, with both quantitative and qualitative assessments. Patient Mrs. H, 55 years old, has internal risk aspects in the form of gender, age factor >50 years, lack of knowledge about vertigo, curative treatment patterns, fatigue and excessive stress. External risk aspects of the patient are lack of family knowledge about vertigo, curative family treatment patterns, and lack of emotional and practical support from the family for the patient's daily activities. After the intervention, there was improvement in the clinical symptoms of vertigo in patients, increased patient knowledge about vertigo, and changes in patient treatment patterns. Keyword: Benign Paroxysmal Positional Vertigo, Family Medicine